Sustainability Assessment of a District-Wide Quality Improvement on Newborn Care Program in Rural Rwanda: A Mixed-Method Study. Issue 1 (19th April 2021) - Nahimana, Evrard; Magge, Hema; Bizimana, Francois; Nyishime, Merab; Lively, Christina Thompson; Gilbert, Hannah; Gauthier, Bethany Hedt; Sayinzoga, Felix; Nkikabahizi, Fulgence; Hirschhorn, Lisa R.
Background: Neonatal mortality continues to be a global challenge, particularly in low- and middle-income countries. There is growing work to reduce mortality through improving quality of systems and care, but less is known about sustainability of improvements in the setting post initial implementation. We conducted a 12-month sustainability assessment of All Babies Count (ABC), a district-wide quality improvement project including mentoring and improvement collaborative designed to improve quality and reduce neonatal mortality in two districts in rural Rwanda. Methods: We measured changes in key neonatal process, coverage, and outcome indicators between the completion of ABC implementation and 12 months after the completion. In addition, we conducted 4 focus group discussions and 15 individual in-depth interviews with health providers and facility and district leaders to understand factors that influenced sustainability of improvements. We used an inductive, content analytic approach to derive six themes related to the ABC sustainability to explain quantitative results. Findings: Twelve months after the completion of ABC implementation, we found continued improvements in core quality, coverage, and neonatal outcomes. During ABC, the percentage of women with 4 antenatal visits increased from 12% to 30% and remained stable 12 months post-ABC (30%, p = 0.7) with an increase in facility-based delivery from 92.6% at the end of ABC to 95.8% (p = 0.01) at 12-month post-ABC. During ABC intervention, the 2 districts decreased neonatal mortality from 30.1 to 19.4 deaths per 1, 000 live births with maintenance of the lower mortality 12 months post-ABC (19.4 deaths per 1, 000 live births, p = 0.7). Leadership buy-in and development of self-reliance encouraging internally generated solutions emerged as key factors to sustain improvements while staff turnover, famine, influx of refugees, and unintended consequences of new national newborn care policies threatened sustainability. Interpretation: Despite discontinuity of key ABC support, health facilities kept the momentum of good practices and were able to maintain or increase the level of prenatal, neonatal quality of care and outcomes over a period of 12 months following the end of initial ABC implementation. Additional studies are needed to determine the longer-term sustainability beyond one year.